Self, struggle, and soul: Linking personality, self-concept, and religious/spiritual struggle. (October 2016) - Grubbs, Joshua B.; Wilt, Joshua; Stauner, Nicholas; Exline, Julie J.; Pargament, Kenneth I.
Abstract: Religious and spiritual (r/s) struggles are common experiences and robust predictors of poor mental and physical health outcomes. The present study sought to examine the role of personality and self-concept in predicting r/s struggles both concurrently and longitudinally. Four samples were collected ( total N = 5015), involving three cross-sectional samples of undergraduates and a cross-sectional and 1-month longitudinal sample of adult web-users. Across samples, aspects of personality (e.g., low self-esteem, high entitlement, high neuroticism) consistently predicted the concurrent experience of r/s struggles. Longitudinally, facets of self-concept (e.g., low self-esteem, low agreeableness) also predicted r/s struggle, even when baseline levels of r/s struggle were controlled, further demonstrating that personality and self-concept likely play a role in the experience of r/s struggles. Highlights: Personality is related to the experience of religious and spiritual struggle. Personality predicts both total experience of struggle and specific struggles. These relationships are replicable across diverse samples ( N > 5000). Some of these relationships were evident both concurrently and over time.